Highways : the location, design, construction and maintenance of road pavements - O'Flaherty, Coleman A.; Hughes, David (Lecturer in geotechnical and highway engineering) (ICE Publishing, 2016)
The fifth edition of 'Highways' provides a comprehensive view across all aspects of road engineering, encompassing an extensive range of topics from pavement design, earthworks, and skid resistance to subsurface moisture control, surface drainage and construction of hot-mix bituminous roadbases and surfacings. This book shares the insights and practical experiences of industry experts who present the multifaceted aspects of road engineering to those seeking to discover more about these themes.
Previous edition: Oxford : Butterworth-Heinemann, 2002.
Keywords: Highway engineering -- Great Britain.; elektronické knihy; electronic books